The Emergence Of Islamic Unit Trust Fund And Its Performance - Lai, Kian Sin (2006)
This research focuses on th eemergence of Islamic unit trust funds and studies its performance in Malaysia. The performance will be measured by its total return and risk analysis compared with Kuala Lumpur Composite Index and Kuala Lumpur Syariah Index over the same period.